Weed Diversity and their Management in Major Rice-based Cropping Systems in India - Das, Saptashree; Ray, Manabendra; Saha Roy, Aditi; Barat, Subhajit (International Journal of Bio-resource and Stress Management, 2024)
Weeds are unwanted and undesirable plants that interfere with cultivated crops for utilization of natural resources such as nutrients, water, and light, space, causing harbor of insect pests and disease adverse allelopathic effects and increasing cost of production indirectly, reducing crop yield. India is an agrarian country, where cropping systems form the backbone of Indian agriculture. Every cropping system has its associated weeds, and to manage these weeds requires a specific crop management approach. The main rice-based cropping systems in India, such as rice-wheat, rice-rice, rice-pulse, rice-maize, and rice-oilseed, have been pivotal in ensuring food security. However, these systems face significant challenges due to weed infestations, leading to yield losses ranging from 13% to 97%. Weeds like grass, sedge and broad-leaf weed varieties pose a substantial threat to these crops, particularly in direct-seeded conditions. To manage weeds effectively, various approaches are employed, including crop rotation, tillage, herbicide application, and intercropping. For instance, in rice-wheat systems, zero-tillage practices, crop residue mulch, and early sowing help to reduce weed emergence. In rice-pulse systems, pre-emergence herbicides, hand weeding, and intercropping prove effective. Maize-based systems benefit from tillage, mulching, and planting at closer spacing. Weed management is critical to sustaining rice-based cropping systems and ensuring food security in India. Tailored strategies that consider crop-specific challenges are essential to mitigate yield losses and maintain agricultural productivity.